Knowledge and Attitude of Middle-Age Population towards predisposing factors of Hypertension - Sumble Nisar, Sumble Nisar; Tooba Mazhar, Tooba Mazhar; Ifra Arif, Ifra Arif; Fazal Ur Rehman, Fazal Ur Rehman (Students' Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Hypertension is one of the most common diseases affecting middle aged population of the world. It is a “Silent killer” as it is rarely symptomatic Materials & Methods: An interview based cross-sectional study was conducted during 3 months period on a random sample of 323 individuals attending the Out Patient Department of Medicine at Holy Family Hospital, Rawalpindi which is one of the largest Tertiary Care Hospital in Punjab providing health care facilities to a major population of Rawalpindi and nearby areas. A sample size of 323 was calculated using WHO sample size calculator. Normotensive and Middle-aged (WHO verified: 40-60 years) individuals were selected by simple random sampling and interviewed during OPD timings. A self-structured questionnaire was used. The questions pertaining to risk factors, complications and presenting complaints were of multiple response type. Data were entered and analysed on SPSS v 23. Percentages and frequencies were calculated for categorical data. Results: 236 (88.1%) participants considered hypertension as a disease whereas 232 (86.6%) participants thought that blood pressure monitoring was crucial. 160 (59.7%) participants did not know how to read blood pressure reading while 108 (40.3%) participants knew about it. 121 (45.1%) participants had no knowledge about normal reading of blood pressure. 32 (11.9%) participants considered 100/60-110/70 mmHg, 98 (36.6%) considered 120/80-130/90 mmHg and 17 (6.3%) considered 140/100-150/110 mmHg as normal range for blood pressure. Conclusion: Knowledge of middle aged normotensive individuals regarding hypertension is just borderline. Keywords: Knowledge; Attitude; Predisposing Factors; Hypertension